Goal Orientations, Mathematics Self-Efficacy and Cognitive Strategies as Predictors of Students' Mathematics Achievement - Hoo, Heap King (2003)
The purpose of this study is to examine the relationship between students' goal orientations (learning and performance), mathematics self-efficacy, cognitive strategies (deep and shallow) and mathematics achievement. This study also attempts to identify the predictors of deep cognitive strategy, shallow cognitive strategy and mathematics achievement. The sample consisted of 339 Form Four students. Pearson correlation showed that learning goal and mathematics self-efficacy were significantly correlated with each other (r = 0.57, p< .01). Deep cognitive strategy was significantly (p< .01) correlated with learning goal (r = 0.49) and mathematics self-efficacy (r = 0.54). The relationship between these three variables was positive and of moderate strength. Performance goal was positively correlated with shallow cognitive strategy (r = 0.18, p< .01), but the relationship was slight. Mathematics achievement was significantly (p< .01) correlated with learning goal (r = 0.22), mathematics self-efficacy (r = 0.30) and deep cognitive strategy (r = 0.20). In contrast, mathematics achievement was negatively correlated with performance goal (r = -0.16, p< .01) and shallow cognitive strategy (r = -0.11, p< .05), but the correlations for all these were considered weak. Stepwise multiple regression analyses were utilized to identify the predictors of deep cognitive strategy, shallow cognitive strategy and mathematics achievement. Results showed that mathematics self-efficacy and learning goal were significant predictors of deep cognitive strategy. Both learning goal and performance goal were significant predictors of shallow cognitive strategy. Mathematics self-efficacy, performance goal and shallow cognitive strategy served as significant predictors of students' mathematics achievement.